Simulation-Based Performance Comparison of TCP Over IPV6 and IPV4 - Habbal, Adib (2006)
Internet Protocol ver-4 (IPv4) has been used for long times ago, but the great growth of the Internet and its change in drastic way over time makes IPv4 face many problems. The main one is the lack in address space, not to forget issues such as mobility and security. To meet requirements that didn't exist in IPv4, IP version 6 (IPv6) was designed. TCP protocol is as fundamental as IP protocol in the TCP/IP Protocol Suite. TCP adds some mechanisms to overcome unreliability and connectionless IP functionalities so can guarantee delivery the messages. In this project, we investigated the impact of using IPv6 on the behavior of TCP by comparing the performance of TCP over IPv6 and IPv4. TCP Reno (one of TCP flavors)is used in the comparison; NS-2 and OMNeT++ are tools used to perform the simulation experiments. During the course of simulations, throughput and delay (measured RTT) of TCP over IPv6 and 1Pv4 have been studied, and two different type of traffic (FTP,HTTP) are generated on same network topology with two scenarios run for each type of traffic (single flow, compete flow). Project results have shown a poor performance of TCP over IPv6 in terms of a lot of packet loss and long delay (measured RTT).